Pengembangan Karir Dalam Era Ambiguitas - Helen Novita Sari; Nur Rahmania; Mochammad Isa Anshori (Pusat Riset dan Inovasi Nasional, 2023)
Career development in an era of ambiguity is becoming increasingly important in the modern era of uncertainty and rapid environmental change. The ever-changing business, social, and technological environments pose new challenges for individuals seeking to develop their careers. This research aims to identify career development strategies in the face of an ambiguous work environment, as well as to explore the concepts and practices of career development that exist in this era of ambiguity. This research uses the literature method or literature study, which is by utilizing various literature sources to obtain data. A qualitative approach was chosen because the data produced is in the form of descriptions or words. The results showed that career development is very important in the era of ambiguity, and each individual needs to integrate flexibility, adaptability, and understanding of uncertainty in their career development strategy. With a deep understanding of ambiguity and the ability to adapt, individuals can maximize their career potential in this era of change. Organizations can also support employees by creating an environment that enables growth and development amidst rapid change.